THE EFFECT OF USING KAHOOT EDUCATIONAL GAME MEDIA ON STUDENTS' LEARNING OUTCOMES IN PANCASILA EDUCATION LEARNING ON SOCIAL AND CULTURAL DIVERSITY MATERIALS IN CLASS IV OF SDN 32 BANDA ACEH - Maulani, Ade Ria; Mislinawati, Mislinawati; Nurmasyitah, Nurmasyitah (Elementary Education Research, 2025)
The learning process still focuses on the teacher and does not utilize technological media, thus affecting learning outcomes that are not optimal. One solution that can be used is the use of interactive learning media, based on Kahoot educational game media. This study was conducted with the aim of knowing the effect of using Kahoot educational game media on student learning outcomes in Pancasila education learning material on social and cultural diversity in class IV SDN 32 Banda Aceh. This study used a quantitative approach with the type of research Quasi Experimental and Nonequivalent Control Group Design. The population in this study involved all fourth grade students of SDN 32 Banda Aceh, totaling 58 students. The sample in the study was divided into two groups, namely the experimental class totaling 30 students and the control class totaling 28 students selected using the total sampling technique. Data collection was carried out through giving pre-test and post-test using an instrument in the form of a multiple choice test consisting of 20 questions. To measure significant differences in learning outcomes between experimental and control classes, researchers used the Mann-Whitney test. The results of data analysis showed the value of Asymp. Sig. (2-tailed) value of 0.000 0.05, which indicates a significant difference between learning outcomes using Kahoot educational game media and conventional learning, so Ha is accepted and H0 is rejected. The conclusion in this study is that there is an effect of using Kahoot educational game media on student learning outcomes in Pancasila education learning material on social and cultural diversity in class IV SDN 32 Banda Aceh.